Preparation method of permanent magnetic ferrite
By using low-cost iron fine powder as the iron source and performing multi-stage oxidation and prefixing treatment in the rotating kiln, the problem of iron source defects of high-performance permanent magnet ferrite materials is solved, and the preparation and cost reduction of high-performance materials are achieved.
Patent Information
- Application Number
- CN202411994170.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-12-31
AI Technical Summary
In the prior art, high-performance permanent magnet ferrite materials have serious iron source defects, resulting in limited development.
High-performance permanent magnet ferrite materials are prepared by using low-cost and high-yield iron fine powder as the iron source, and multi-stage oxidation is performed through external heating segmented rotary kilns. Combined with reasonable molar ratio and optimization of the prefiring stage, high-performance permanent magnet ferrite materials are prepared.
The preparation of high-performance permanent magnet ferrite materials is realized, which meets the high requirements of residual magnetism and intrinsic coercive forces, while reducing raw material costs and broadening the selection range of raw materials.
Smart Images

Figure CN119912249A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnetic material preparation, and in particular relates to a method for preparing a permanent magnetic ferrite. Background Art
[0002] my country is a major producer of magnetic materials. Permanent ferrite, as a type of magnetic material, is currently the most widely used magnetic material. It is widely used in driving or starting motors in motorcycles, automobiles, office automation, audio, stereos, and video recorders. In addition, it is also widely used in household appliances and power tools such as washing machines, microwave ovens, variable frequency air conditioners, and refrigerators. With the development trend of miniaturization and thinness of various electronic and electrical products, the demand for high-performance permanent ferrite materials is increasing. At present, the iron source of high-performance permanent ferrite materials is basically inseparable from red iron oxide as a production raw material.
[0003] The patent application document with publication number CN101786869B discloses a calcium permanent magnet ferrite material and a preparation method thereof, which can make the remanence Br value reach 4200-4700Gs and the intrinsic coercivity Hcj value reach 4500-6200KOe at a sintering temperature of 1150°C or lower. However, its iron source is Fe2O3, and red iron oxide is a by-product of steel mills with limited sources and large price fluctuations. It also contains acidic chlorine or sulfide that is highly corrosive. High-end red iron oxide is in short supply and has a high cost price.
[0004] In order to reduce costs, researchers use other iron source materials such as iron scale or iron concentrate to replace red iron carbide, but the magnetic properties obtained by this method are relatively low, and the magnetic properties are difficult to meet the requirements of high-performance permanent magnet ferrite materials. The patent application document with publication number CN114163226A discloses a method for preparing strontium permanent magnet ferrite pre-sintered materials using super iron concentrate, and proposes to use super iron concentrate with the same particle size as strontium carbonate as raw material, and use the hot flue gas in the rotary kiln to heat exchange with the ball material, and oxidize the ferric oxide in the ball material into ferric oxide to prepare ferrite pre-sintered materials. Although this method proposes to use super iron concentrate to replace red iron oxide production, the oxygen content of the hot flue gas in the rotary kiln used is much lower than the oxygen content in the air, which will lead to a low degree of oxidation of FeO in the iron concentrate, and the intrinsic coercive Hcj value in the magnetic properties obtained is only 3000-3200Oe, which is low performance.
[0005] Therefore, the iron source defects of high-performance permanent magnet ferrite materials seriously restrict the development of high-performance permanent magnet ferrite materials. Summary of the invention
[0006] The object of the present invention is to provide a method for preparing permanent magnetic ferrite, which adopts low-cost and high-yield raw materials to manufacture high-performance permanent magnetic ferrite materials.
[0007] The purpose of the present invention can be achieved by the following technical solutions:
[0008] The present invention provides a method for preparing a permanent magnetic ferrite, comprising the following steps:
[0009] Step 1, the iron ore concentrate is placed in an externally heated sectional rotary kiln, dried and multi-stage oxidized under negative pressure, and after cooling and discharging, primary grinding and mixing are performed to obtain iron oxide concentrate, the Fe2O3 conversion rate of the iron oxide concentrate is ≥96%, the FeO mass content is ≤1.2wt%, the particle size is ≤5μm, and the Fe2O3 conversion rate is calculated as (FeO mass content before oxidation-FeO mass content after oxidation) / FeO mass content before oxidation×100%.
[0010] Step 2: Evenly mix the iron oxide concentrate, strontium carbonate, calcium carbonate, lanthanum oxide, cobalt oxide, sodium carbonate and boric acid to obtain a mixture, mix it with water, and then perform secondary grinding to obtain a slurry;
[0011] Step 3: Dehydrate and concentrate the slurry to obtain a thick slurry with a solid content of 65-85%. The thick slurry is pre-burned in a rotary kiln to obtain a loose density of 2.5-3.0 g / cm 3 The dense granular material is crushed by dry ball milling to obtain a pre-burned material of 4 to 6 μm, which is mixed with water at a mass ratio of 1:1 to 2.3, and an additive is added for secondary continuous ball milling to obtain a fine slurry with an average particle size of 0.8 to 1.1 μm;
[0012] Step 4: After the fine slurry is concentrated to a solid content of 65-75%, it is pressed into shape under a magnetic field. The molded body is sintered in air at a sintering temperature of 1190-1240° C. for 2-4 hours to obtain a permanent magnet ferrite material.
[0013] Furthermore, the iron ore concentrate is a 200-mesh sieve, and its components include 70-72wt% Fe, 28-31wt% FeO, ≤0.35wt% SiO2, and 0-12wt% moisture.
[0014] Furthermore, the externally heated sectional rotary kiln can be heated by electricity or gas, and a draft fan is provided at the feeding end, and an air inlet regulating valve and a negative pressure gauge are provided at the discharging end.
[0015] Furthermore, in step 1, the parameters of the iron ore concentrate in the externally heated segmented rotary kiln are set as follows:
[0016] First-stage heating section: 250~350℃, second-stage heating section: 350℃~550℃, third-stage heating section: 550~650℃, fourth-stage heating section: 650℃~750℃, fifth-stage heating section: 750~850℃;
[0017] The iron ore concentrate stays in the first and third heating sections for 0.5 to 1 h, in the fifth heating section for 1 to 3 h, and in the second and fourth heating sections for less than 0.5 h.
[0018] Iron ore concentrate is subjected to multi-stage oxidation in an externally heated sectional rotary kiln. By controlling the residence time of the iron ore concentrate at different temperatures and utilizing the difference in reaction free energy of the iron ore concentrate at different temperatures, its organizational morphology and internal structure are changed, so that most of the FeO in the iron ore concentrate is converted into Fe2O3. From a microstructural point of view, the morphology changes from particle to flocculent, the pores in the structure become larger, and the activity of the particles is enhanced, which is conducive to the subsequent solid-phase reaction and ion substitution with strontium, calcium, lanthanum, cobalt, etc. at high temperature, and high-performance ferrite materials can be prepared.
[0019] Furthermore, in step 1, the negative pressure is -30 to -5 Pa.
[0020] The oxidation of iron ore concentrate under negative pressure can make the oxygen content in the rotary kiln sufficient to meet the oxygen demand of FeO during oxidation and ensure the oxidation effect.
[0021] Furthermore, the first-stage grinding equipment is a through-type ball mill with a rotation speed of 28 to 34 r / min, a processing capacity of 1.5 to 3 t / h, and a grinding medium of Grinding balls.
[0022] Furthermore, in step 2, the mass fractions of the components of the mixture are as follows:
[0023] 80-84 parts of iron oxide powder, 0.5-3 parts of strontium carbonate, 4-5 parts of calcium carbonate, 7-9 parts of lanthanum oxide, 1.5-3 parts of cobalt oxide, 0-0.3 parts of sodium carbonate, and 0-0.3 parts of boric acid;
[0024] The value of (molar amount of iron oxide concentrate + molar amount of cobalt oxide × 3 / 2) / (molar amount of strontium carbonate + molar amount of calcium carbonate + molar amount of lanthanum oxide × 2) is 4.9 to 5.5.
[0025] Furthermore, the secondary grinding equipment is a pot mill or a sand mill, the grinding time is 5 to 10 hours, and the grinding medium is Grinding balls.
[0026] Furthermore, in step 2, the slurry is tested for particle size by air permeability method, and the particle size is ≤1.5 μm, and the content of matter on a 200-mesh standard sieve is ≤0.5%.
[0027] Furthermore, the setting of pre-burning the concentrated slurry in the rotary kiln is as follows:
[0028] The thick slurry stays in the temperature range of 600-900°C for 2-3 hours and is kept warm in the temperature range of 1100-1250°C for 0.5-2 hours.
[0029] Furthermore, during pre-firing of the rotary kiln, the air volume of the combustion-supporting fan is increased so that the residual oxygen content in the tail gas is ≥8%.
[0030] Furthermore, in step 3, the additives include calcium carbonate, calcium gluconate and silicon powder, which are added according to their mass fractions in the secondary continuous ball milling slurry, and their mass fractions are as follows:
[0031] Calcium carbonate 0.4-1.0%, calcium gluconate 0.05-0.4%, silicon micropowder 0-0.35%.
[0032] Furthermore, in step 4, the magnetic field strength of the magnetic field is ≥ 7000 Oe.
[0033] Furthermore, the silicon content of the permanent magnetic ferrite material is ≤0.4wt%, and is detected using a fluorescence analyzer from Rigaku Corporation.
[0034] By limiting the silicon content contained in the additive to control the silicon content of the permanent magnet ferrite material to ≤0.4wt%, it is possible to prevent excessive silicon in the ferrite material and avoid the generation of silicates, which will combine with calcium and strontium in the ferrite material to cause performance deterioration.
[0035] Beneficial effects of the present invention:
[0036] (1) In the ferrite preparation method provided by the present invention, the iron source is low-cost and high-yield iron concentrate, which completely replaces red iron oxide to prepare high-performance ferrite materials, broadens the selection range of high-performance permanent magnet ferrite raw materials, reduces the cost of raw materials, and can generate greater economic benefits; the application of iron concentrate in the oxidation route is expanded from only being able to produce medium and low-grade magnetic materials to the production of high-performance magnetic materials, thereby improving its use value.
[0037] (2) The ferrite preparation method provided by the present invention comprises multi-stage grinding and homogenization of the iron ore concentrate, that is, firstly using a dry through-type ball mill to fill with larger grinding media for coarse grinding, and then using a wet method to fill with smaller grinding media for fine grinding. The graded grinding can effectively improve the grinding efficiency and reduce the electricity cost; the homogenization after the first-stage grinding can make the silicon content in the iron ore concentrate consistent. Generally, the intrinsic coercive force of high-performance magnetic materials is more sensitive to the silicon element, so the fluctuation of the silicon content is avoided, and the stability of the performance of the high-performance magnetic materials is improved.
[0038] (3) In the ferrite preparation method provided by the present invention, the residence time of the pre-sintering stage is extended at 600-900°C, and the CO2 released when the added raw materials calcium carbonate and strontium carbonate are decomposed is used to make the material structure looser, generate gaps between the materials, and increase the combustion-supporting air volume to increase the residual oxygen content in the tail gas, so that the iron concentrate is completely oxidized and converted into Fe2O3, avoiding Fe 2+Risk of residual magnetic properties degradation.
[0039] (4) The ferrite preparation method provided by the present invention adopts iron concentrate as the iron source and selects a reasonable molar ratio to prepare the ferrite material, so as to achieve a permanent magnet ferrite with a remanence of ≥4350Gs and an intrinsic coercive force of ≥5400Oe. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] The present invention will be further described below in conjunction with the accompanying drawings.
[0041] Figure 1 is a SEM image of the iron oxide concentrate prepared in Example 6 of the present invention;
[0042] Figure 2 It is a SEM picture of the iron oxide concentrate prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0043] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] Example 1
[0045] This embodiment provides a method for preparing a permanent ferrite, and the specific steps are as follows:
[0046] Step 1: Place the iron ore concentrate in an externally heated segmented rotary kiln with an induced draft fan at the feed end and an air inlet regulating valve and a negative pressure gauge at the discharge end. The iron ore concentrate is dried and multi-stage oxidized in a negative pressure environment of -30 to -5 Pa. After the material in the rotary kiln is cooled and discharged, it enters a through-type ball mill for primary grinding. After grinding, it enters a mixer for homogenization to obtain iron oxide concentrate with a particle size of ≤5μm.
[0047] The iron concentrate is the product under the 200-mesh sieve, and its composition includes 71wt% of Fe element, 30wt% of FeO, 0.32wt% of SiO2 and 2wt% of water.
[0048] The parameters of iron ore concentrate in the externally heated sectional rotary kiln are set as follows:
[0049] First-stage heating section: 250~350℃, second-stage heating section: 350℃~550℃, third-stage heating section: 550~650℃, fourth-stage heating section: 650℃~750℃, fifth-stage heating section: 750~850℃;
[0050] The iron ore concentrate stays in the first and third heating sections for 1 hour respectively, in the fifth heating section for 2 hours, and in the second and fourth heating sections for 0.4 hours each.
[0051] The speed of the through ball mill is 30r / min, and the grinding medium is Grinding balls.
[0052] The Fe2O3 conversion rate of the iron oxide concentrate is 96.6%, the FeO mass content is 1.0%, the particle size is ≤5μm, and the Fe2O3 conversion rate is calculated as (FeO mass content before oxidation-FeO mass content after oxidation) / FeO mass content before oxidation×100%.
[0053] Step 2: Evenly mix the iron oxide concentrate, strontium carbonate, calcium carbonate, lanthanum oxide, cobalt oxide, sodium carbonate and boric acid to obtain a mixture, mix it with water, and perform secondary grinding to obtain a slurry. The particle size is tested by air permeability method. The particle size is ≤1.5μm, and the material on the 200-mesh standard sieve is ≤0.5%.
[0054] Among them, the mass fractions of each component of the mixture are as follows:
[0055] 84 parts of iron oxide powder, 2.8 parts of strontium carbonate, 4.1 parts of calcium carbonate, 8 parts of lanthanum oxide, 2.0 parts of cobalt oxide, 0.3 parts of sodium carbonate, and 0.1 parts of boric acid.
[0056] The value of (molar amount of iron oxide concentrate + molar amount of cobalt oxide × 3 / 2) / (molar amount of strontium carbonate + molar amount of calcium carbonate + molar amount of lanthanum oxide × 2) is 5.19 (the molar amount of iron oxide concentrate is calculated according to the mass of iron oxide concentrate / relative molecular weight of iron oxide).
[0057] The equipment for secondary grinding is a sand mill, the grinding time is 8h, and the grinding medium is Grinding balls.
[0058] Step 3: Dehydrate and concentrate the slurry to obtain a concentrated slurry with a solid content of 70%. The concentrated slurry is pre-burned in a rotary kiln to obtain a bulk density of 2.7 g / cm 3 The dense granular material is prepared by increasing the air volume of the combustion-supporting fan during pre-firing in the rotary kiln so that the residual oxygen content in the tail gas is ≥8%. The pre-firing material of 4-6μm is obtained by dry ball milling, and mixed with water at a mass ratio of 1:1. Additives are added for secondary continuous ball milling. The additives include calcium carbonate, calcium gluconate and silicon micropowder. Calculated by the mass fraction in the secondary continuous ball milling slurry, the content of calcium carbonate is 0.8wt%, the content of calcium gluconate is 0.1wt%, and the content of silicon micropowder is 0.35wt%, and a fine slurry with an average particle size of 1.0μm is obtained.
[0059] The setting of pre-burning thick slurry in rotary kiln is as follows:
[0060] The thick slurry stays in the temperature range of 600-900°C for 3 hours and is kept warm in the temperature range of 1100-1250°C for 1 hour.
[0061] Step 4: After the fine slurry is concentrated to a solid content of 75%, it is pressed into a magnetic field with a magnetic field strength of 7000Oe. The molded body is sintered in air at a sintering temperature of 1190-1240°C and kept warm for 4 hours to obtain a permanent magnetic ferrite material. The silicon content of the permanent magnetic ferrite material is ≤0.4wt% using a fluorescence analyzer from Rigaku Corporation.
[0062] Example 2
[0063] The only difference from Example 1 is that the mass fractions of the components of the mixture in step 2 are different, and the value of (mol amount of iron oxide concentrate + molar amount of cobalt oxide × 3 / 2) / (mol amount of strontium carbonate + molar amount of calcium carbonate + molar amount of lanthanum oxide × 2) is controlled to be 5.23. The other conditions and steps are the same as those in Example 1. The mass fractions of the components of the mixture are as follows:
[0064] 84 parts of iron oxide powder, 2.8 parts of strontium carbonate, 4.1 parts of calcium carbonate, 8 parts of lanthanum oxide, 2.2 parts of cobalt oxide, 0.2 parts of sodium carbonate, and 0.2 parts of boric acid.
[0065] Example 3
[0066] The only difference from Example 1 is that the mass fractions of the components of the mixture in step 2 are different, and the value of (mol amount of iron oxide concentrate + molar amount of cobalt oxide × 3 / 2) / (mol amount of strontium carbonate + molar amount of calcium carbonate + molar amount of lanthanum oxide × 2) is controlled to be 4.94. The other conditions and steps are the same as those in Example 1. The mass fractions of the components of the mixture are as follows:
[0067] 83 parts of iron oxide powder, 0.9 parts of strontium carbonate, 5 parts of calcium carbonate, 9 parts of lanthanum oxide, 1.5 parts of cobalt oxide, 0.1 parts of sodium carbonate, and 0.3 parts of boric acid.
[0068] Example 4
[0069] The only difference from Example 1 is that the mass fractions of the components of the mixture in step 2 are different, and the value of (mol amount of iron oxide concentrate + molar amount of cobalt oxide × 3 / 2) / (mol amount of strontium carbonate + molar amount of calcium carbonate + molar amount of lanthanum oxide × 2) is controlled to be 4.98. The other conditions and steps are the same as those in Example 1. The mass fractions of the components of the mixture are as follows:
[0070] 80 parts of iron oxide powder, 1.1 parts of strontium carbonate, 5 parts of calcium carbonate, 9 parts of lanthanum oxide, 3 parts of cobalt oxide, 0.1 parts of sodium carbonate, and 0.3 parts of boric acid.
[0071] Example 5
[0072] The only difference from Example 1 is that the mass fractions of the components of the mixture in step 2 are different, and the value of (mol amount of iron oxide concentrate + molar amount of cobalt oxide × 3 / 2) / (mol amount of strontium carbonate + molar amount of calcium carbonate + molar amount of lanthanum oxide × 2) is controlled to be 5.45. The other conditions and steps are the same as those in Example 1. The mass fractions of the components of the mixture are as follows:
[0073] 84 parts of iron oxide powder, 2 parts of strontium carbonate, 4.0 parts of calcium carbonate, 8.8 parts of lanthanum oxide, 3 parts of cobalt oxide, 0.1 parts of sodium carbonate, and 0.3 parts of boric acid.
[0074] Example 6
[0075] The only difference from Example 1 is that the mass fractions of the components of the mixture in step 2 are different, and the value of (mol amount of iron oxide concentrate + molar amount of cobalt oxide × 3 / 2) / (mol amount of strontium carbonate + molar amount of calcium carbonate + molar amount of lanthanum oxide × 2) is controlled to be 5.09. The other conditions and steps are the same as those in Example 1. The mass fractions of the components of the mixture are as follows:
[0076] 84 parts of iron oxide powder, 2.8 parts of strontium carbonate, 5.0 parts of calcium carbonate, 7.5 parts of lanthanum oxide, 3 parts of cobalt oxide, 0.1 parts of sodium carbonate, and 0.3 parts of boric acid.
[0077] The electron microscope image of the iron oxide powder prepared in this example is shown in Figure 1 .
[0078] Comparative Example 1
[0079] Compared with Example 4, in step 1 of this comparative example, no induced draft fan is provided at the feeding end of the externally heated segmented rotary kiln, and natural exhaust is adopted. Other conditions and steps are the same as those in Example 4.
[0080] At this time, the Fe2O3 conversion rate of the iron oxide concentrate is 81.3%, the FeO mass content is 5.6%, the particle size is ≤5μm, and the Fe2O3 conversion rate is calculated as (FeO mass content before oxidation-FeO mass content after oxidation) / FeO mass content before oxidation×100%.
[0081] Comparative Example 2
[0082] Compared with Example 6, in step 1 of this comparative example, the iron ore concentrate is not subjected to multi-stage oxidation in the externally heated segmented rotary kiln, but is directly heated and oxidized. Other conditions and steps are the same as those in Example 4.
[0083] The parameters of iron ore concentrate in the externally heated sectional rotary kiln are set as follows:
[0084] The heating temperature is 750-850°C and the residence time is 3h.
[0085] At this time, the Fe2O3 conversion rate of the iron oxide concentrate is 89.3%, the FeO mass content is 3.2%, the particle size is ≤5μm, and the Fe2O3 conversion rate is calculated as (FeO mass content before oxidation-FeO mass content after oxidation) / FeO mass content before oxidation×100%.
[0086] The electron microscope image of the iron oxide concentrate prepared in this comparative example is shown in Figure 2 .
[0087] Comparative Example 3
[0088] Compared with Example 1, in step 3 of this comparative example, the residence time at 600-900°C in the rotary kiln pre-sintering is 1h, the combustion-supporting air volume is not increased, and the residual oxygen content in the tail gas is 6%. At this time, the bulk density of the dense granules is 2.4g / cm 3 , other conditions and steps are the same as in Example 1.
[0089] Comparative Example 4
[0090] Compared with Example 6, the amount of additive added in step 3 of this comparative example is different, and other conditions and steps are the same as Example 1.
[0091] At this time, the additives include calcium carbonate, calcium gluconate and silicon micropowder. Calculated by the mass fraction in the secondary continuous ball milling slurry, the calcium carbonate content is 0.8wt%, the calcium gluconate content is 0.1wt%, and the silicon micropowder content is 0.4wt%.
[0092] Using a fluorescence analyzer produced by Rigaku Corporation of Japan, the silicon content of the permanent magnetic ferrite material prepared in this comparative example was 0.45 wt %.
[0093] Comparative Example 5
[0094] Compared with Example 1, the mass fractions of the components of the mixture in step 2 of this comparative example are different, and the value of (mol amount of iron oxide concentrate + molar amount of cobalt oxide × 3 / 2) / (mol amount of strontium carbonate + molar amount of calcium carbonate + molar amount of lanthanum oxide × 2) is 5.59. The other conditions and steps are the same as those in Example 1. The mass fractions of the components of the mixture are as follows:
[0095] 86 parts of iron oxide powder, 2.0 parts of strontium carbonate, 3.5 parts of calcium carbonate, 9.5 parts of lanthanum oxide, 3.0 parts of cobalt oxide, 0.2 parts of sodium carbonate, and 0.2 parts of boric acid.
[0096] Comparative Example 6
[0097] Compared with Example 1, the mass fractions of the components of the mixture in step 2 of this comparative example are different, and the value of (mol amount of iron oxide concentrate + molar amount of cobalt oxide × 3 / 2) / (mol amount of strontium carbonate + molar amount of calcium carbonate + molar amount of lanthanum oxide × 2) is 4.82. The other conditions and steps are the same as those in Example 1. The mass fractions of the components of the mixture are as follows:
[0098] 76 parts of iron oxide powder, 2.3 parts of strontium carbonate, 4.5 parts of calcium carbonate, 7 parts of lanthanum oxide, 1.2 parts of cobalt oxide, 0.2 parts of sodium carbonate, and 0.2 parts of boric acid.
[0099] Comparative Example 7
[0100] Compared with Example 1, the mass fractions of the components of the mixture in step 2 of this comparative example are different, and the value of (mol amount of iron oxide concentrate + molar amount of cobalt oxide × 3 / 2) / (mol amount of strontium carbonate + molar amount of calcium carbonate + molar amount of lanthanum oxide × 2) is 5.55. The other conditions and steps are the same as those in Example 1. The mass fractions of the components of the mixture are as follows:
[0101] 76 parts of iron oxide powder, 1.8 parts of strontium carbonate, 3.6 parts of calcium carbonate, 6.8 parts of lanthanum oxide, 1.2 parts of cobalt oxide, 0.2 parts of sodium carbonate, and 0.2 parts of boric acid.
[0102] The permanent magnet ferrite materials prepared in Examples 1 to 6 and Comparative Examples 1 to 7 were tested, and the results are shown in Table 1:
[0103] Table 1
[0104]
[0105]
[0106] As can be seen from Table 1, in the embodiment, by adjusting the molar ratio in the mixture and optimizing the formula ratio, the permanent ferrite remanence ≥ 4350Gs and the intrinsic coercivity ≥ 5400Oe are achieved. In Comparative Example 1, the iron ore concentrate was not naturally oxidized by exhaust in a negative pressure environment. The FeO content in the iron ore concentrate after oxidation was 5.6% by chemical titration. The ferrous iron content was too high and could not be completely oxidized by subsequent processes, resulting in reduced performance. In Comparative Example 2, the iron ore concentrate was not subjected to multi-stage oxidation in a rotary kiln. Figure 1 and Figure 2The SEM images of the comparison show that the microstructure of the iron oxide powder obtained by multi-stage oxidation is basically flocculent and has good activity, while the microstructure of the iron oxide powder without multi-stage oxidation is granular and has poor activity, resulting in reduced performance; in Comparative Example 3, the residence time at 600-900°C in the pre-burning stage was not extended, the combustion-supporting air volume was not increased, and the residual oxygen content in the tail gas was too low at 6%, resulting in the residual FeO not being completely oxidized, thereby resulting in reduced performance; in Comparative Example 4, the silicon content in the prepared permanent magnet ferrite material was 0.45% detected by a fluorescence analyzer of Rigaku Japan, which exceeded 0.4%. Excessive silicon leads to the production of silicates, which will combine with calcium and strontium in the ferrite material to precipitate, resulting in deterioration of performance. In Comparative Examples 5-7, the molar ratio during batching was outside the range of 4.9-5.5, resulting in deviations in the composition structure of the ferrite material and reduced performance.
[0107] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0108] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a permanent magnetic ferrite, characterized in that: The following steps are involved: Step 1, the iron ore concentrate is placed in an externally heated sectional rotary kiln, dried and multi-stage oxidized under negative pressure, and after cooling and discharging, primary grinding and mixing are performed to obtain iron oxide concentrate, wherein the Fe2O3 conversion rate of the iron oxide concentrate is ≥96%, the FeO mass content is ≤1.2%, and the particle size is ≤5μm; Step 2: Evenly mix the iron oxide concentrate, strontium carbonate, calcium carbonate, lanthanum oxide, cobalt oxide, sodium carbonate and boric acid to obtain a mixture, mix it with water, and then perform secondary grinding to obtain a slurry; Step 3: Dehydrate and concentrate the slurry to obtain a thick slurry with a solid content of 65-85%. The thick slurry is pre-burned in a rotary kiln to obtain a loose density of 2.5-3.0 g / cm 3 The dense granular material is crushed by dry ball milling to obtain a pre-burned material of 4 to 6 μm, which is mixed with water at a mass ratio of 1:1 to 2.3, and an additive is added for secondary continuous ball milling to obtain a fine slurry with an average particle size of 0.8 to 1.1 μm; Step 4: After the fine slurry is concentrated to a solid content of 65-75%, it is pressed into a shape under a magnetic field. The molded body is sintered in air at a sintering temperature of 1190-1240° C. for 2-4 hours to obtain a permanent magnet ferrite material.
2. The method for preparing a permanent magnetic ferrite according to claim 1, characterized in that: The iron concentrate is a product under a 200-mesh sieve, wherein the Fe content is 70-72wt%, the FeO content is 28-31wt%, the SiO2 content is ≤0.35wt%, and the moisture content is 0-12wt%.
3. The method for preparing a permanent magnetic ferrite according to claim 1, characterized in that: In step 1, the parameters of the iron ore concentrate in the externally heated segmented rotary kiln are set as follows: First-stage heating section: 250~350℃, second-stage heating section: 350℃~550℃, third-stage heating section: 550~650℃, fourth-stage heating section: 650℃~750℃, fifth-stage heating section: 750~850℃; The iron ore concentrate stays in the first and third heating sections for 0.5 to 1 h, in the fifth heating section for 1 to 3 h, and in the second and fourth heating sections for less than 0.5 h.
4. The method for preparing a permanent magnetic ferrite according to claim 1, characterized in that: In step 1, the negative pressure is -30 to -5 Pa.
5. The method for preparing a permanent magnetic ferrite according to claim 1, characterized in that: In step 2, the mass fractions of each component of the mixture are as follows: 80-84 parts of iron oxide powder, 0.5-3 parts of strontium carbonate, 4-5 parts of calcium carbonate, 7-9 parts of lanthanum oxide, 1.5-3 parts of cobalt oxide, 0-0.3 parts of sodium carbonate, and 0-0.3 parts of boric acid; The value of (molar amount of iron oxide concentrate + molar amount of cobalt oxide × 3 / 2) / (molar amount of strontium carbonate + molar amount of calcium carbonate + molar amount of lanthanum oxide × 2) is 4.9 to 5.
5.
6. The method for preparing a permanent magnetic ferrite according to claim 1, characterized in that: In step 2, the particle size of the slurry is tested by air permeability method, the particle size is ≤1.5 μm, and the content of the material on the 200-mesh standard sieve is ≤0.5%.
7. The method for preparing a permanent magnetic ferrite according to claim 1, characterized in that: The setting of pre-burning the thick slurry in the rotary kiln is as follows: The thick slurry stays in the temperature range of 600-900°C for 2-3 hours and is kept warm in the temperature range of 1100-1250°C for 0.5-2 hours.
8. The method for preparing a permanent magnetic ferrite according to claim 1, characterized in that: In step 3, the additives include calcium carbonate, calcium gluconate and silicon powder, which are added according to their mass fractions in the secondary continuous ball milling slurry, and their mass fractions are as follows: Calcium carbonate 0.4-1.0%, calcium gluconate 0.05-0.4%, silicon micropowder 0-0.35%.
9. The method for preparing a permanent magnetic ferrite according to claim 1, characterized in that: In step 4, the magnetic field strength of the magnetic field is ≥ 7000 Oe.
10. The method for preparing a permanent magnetic ferrite according to claim 1, characterized in that: The silicon content of the permanent magnet ferrite material is ≤0.4wt%.
Citation Information
Patent Citations
High performance strontium-calcium permanent magnetic ferrite magnet and preparation method thereof
CN104692785A
Preparation method for permanent magnet ferrite
CN107673755A
Method for preparing permanent magnetic ferrite by using ultra-pure magnetite concentrate as raw material
CN113698192A
Method for preparing strontium permanent magnetic ferrite pre-sintering material by using super fine iron powder
CN114163226A
Manufacture of oxide permanent magnet
JP1984197103A